INVESTIGATION OF THE EFFECT OF THE PRIMARY NOZZLE THROAT DIAMETER ON THE EVAPORATOR PERFORMANCE OF AN EJECTOR EXPANSION REFRIGERATION CYCLE - (:unkn) unknown (YILDIZ TECHNICAL UNIV, 2018)
The present work aims to perform the thermodynamic analysis of an ejector expansion refrigeration cycle (EERC) with a constant-pressure two phase flow ejector and to present the effect of primary nozzle throat diameter on cooling capacity of the EERC. The refrigerant is R134a. In order to achieve these objectives, a computational program is developed using EES software to simulate the system. Mathematical modeling of EERC and applied computational procedure are reported in detail. Operation under critical mode is favorable in ejector operation in terms of high entrainment ratio and enhanced ejector performance. As a result, in this present study, ejector of the refrigeration cycle operates under critical conditions and normal shock occurs at the end of the constant area mixing section. Not an iteration process but Henry and Fauske model is applied to determine the physical properties of the fluid under critical conditions.
Keywords: Ejector; Ejector Expansion Refrigeration; Constant-Pressure Ejector; Two-Phase Ejector; 2-PHASE EJECTOR; DESIGN; OPTIMIZATION; ENERGY; HEAT